Integrated risk analyses as part of national climate risk assessments: lessons learnt from the climate risk assessment of Germany - Walter Kahlenborn; Maike Voss; Luise Porst; Marc Zebisch; Kathrin Renner; Inke Schauser (International Journal of Climate Change Strategies and Management)
Purpose – Climate risk assessments (CRAs) become more and more necessary to prepare and prioritise adaptation action. On a policy level, the results of CRAs offer the foundation for national adaptation strategies. However, existing CRAs oftentimes do not exploit their full potential by means of an integrated assessment, i.e. to illustrate the complexity of cascading risks, provide cross-sectoral results, integrate adaptive capacity and demonstrate spatial patterns. This paper seeks to fill this gap by dissecting integrated assessment approaches of national CRAs. Design/methodology/approach – The paper focuses on the integrated analyses of the results of CRAs. Based on a review of selected national, multi-sectoral CRAs, the authors explore the application of such analyses. Additionally, drawing on the latest climate impact and risk assessment for Germany, the authors highlight latest approaches and their implications. Findings – The authors show that even though progress in establishing integrated assessment methods has been made, no common framework exists so far and only few national CRAs include extensive integrated analyses. Nevertheless, the German example demonstrates that integrated analyses can provide a comprehensive overview over risk dynamics, (spatial) patterns and needs for action thus providing practical advice for decision-making on a national adaptation policy level. Originality/value – While it is common knowledge that CRAs in general provide better results, if the models applied are integrated (i.e. combining climate, geo-physical, economic, etc. factors), little attention has been given to the integrated analyses of their results. This paper provides valuable new insight on this aspect which will become far more important in the future.